Dampak Pandemi Covid-19 Terhadap Pendapatan Nelayan Di Kabupaten Merauke - Ranny Kusmita; Rismawati Rismawati; Muhamad Rosyadi Hidayat; Sajriawati Sajriawati (Universitas Musamus, Merauke, Papua, 2021)
Merauke is one of the regencies in Papua Province which is also affected by the COVID-19 pandemic. This is reinforced by the implementation of a lockdown or restrictions on access to and from the area by land, air and sea. The application of restrictions on entry and exit in the Merauke regency is quite long in 2020, which is for approximately two months. This study aims to compare the income of fishermen before the COVID-19 pandemic and during the COVID-19 pandemic in Merauke Regency, as well as to examine the problems faced by fishermen during the COVID-19 pandemic in Merauke Regency. This research was conducted from June to July 20121 with the research locations being Lampu Satu beach in Samkai village, Merauke district and Kumbe beach in Kumbe village, Malind district. These two locations were chosen because they are the centers of the largest fishing population in Merauke Regency. Primary data collection using interview techniques, to 40 respondents who were selected by purposive sampling. Each of the 20 respondents in Lampu Satu waters in Samkai sub-district, Merauke district and 20 respondents in Kumbe waters in Kumbe village, Malind district. The research data was analyzed statistically by looking at the trend and time series of fishermen's income in Merauke Regency. Based on the results of research and discussion, it was concluded that the Covid-19 pandemic had an impact on the income of fishermen in Merauke Regency, both for ship owners, captains/captains, crew members (ABK) and for collectors/collectors of the catch. The impact given is in the form of a decrease in income obtained by fishermen by 58%. The decline in income was caused by constraints in marketing the main catch, namely fish bubbles which became an export commodity abroad during the total lockdown of airport and port access in Papua Province from March to June 2020. The decline in income was also caused by the increase in the number of operational costs in activities. arrests such as the cost of vitamins, medicines, masks and medical tests if needed.